Statutory Protection of Maritime Worker against Economic and Occupational Risks: An Analytical Study - Manair Abubakr Bawadud (International Journal of Law Research and Studies, 2026)
This study examines the statutory protection afforded to maritime workers against economic and occupational risks under the Saudi legal system, in light of the Saudi Labor Law, the Commercial Maritime Law, and the Regulation of Maritime Employment Contracts. Its importance stems from the nature of maritime work, which differs from ordinary work in the workplace, navigation conditions, subordination to the operator and master, and the exceptional risks that may arise during a voyage and affect the employment relationship. The study aims to clarify the concept and characteristics of the maritime employment contract, identify the main risks faced by maritime workers, examine their legal effects, and assess the adequacy of the statutory protections established for them. The study adopts an analytical approach by examining the legal provisions governing maritime employment contracts and evaluating their suitability to the nature of maritime work. It concludes that the maritime employment contract has a special nature that justifies regulating it through provisions distinct from ordinary employment contracts. It also finds that maritime workers may face economic risks, such as voyage cancellation and suspension of navigation, as well as occupational risks related to the maritime environment, which may result in injuries, occupational diseases, or psychological and physical effects. The study further concludes that Saudi law provides safeguards, including wage protection, repatriation expenses, accommodation, medical care, training, compensation, and insurance for occupational injuries. Nevertheless, statutory protection still requires further detail where navigation is suspended for a long period, the voyage cannot be completed, or the seafarer cannot be repatriated.